Influência da alimentação na qualidade da carcaça suína e do pernil para a fabricação do salame tipo italiano - Campos, Rogério Manoel Lemes de (2002)
Sixsty-four pigs during growth and in final growing were used to evaluate the effect of partial substitution of corn by inclusion of rice bran, wheat and cassava meal in swine diet upon the performance, carcass, leg, fat quality and Italian type salami produced with meat and bacon originated from the swine in the four treatments. The performance and feeding costs for 16 pigs in treatment were evaluated based on each kg suine produced. After slaugther 32 carcasses were chosen 8 in treatment, for the evaluation of quality characteristics. In each carcass samples of the leg meat and the bacon were collected to evaluate pH, water holding capacity (WHC), colour, centesimal composition, pigments, fatty acids profile, cholesterol and the microbiological counting. The leg meat and bacon of each carcass were used to produce 32 ties of salamis on which there were executed daily evaluations of pH and weekly evaluations of pigments during 28 maturation days. After elaboration pH, the rate of losses, hundredth composition, pigments and sensorial charactheristics were analised. At the shelf life, on 120 days, pH, centesimal composition, pigments, fatty acids profile, cholesterol, the microbiological millieu, sensorial charactheristics and volatiles compounds were measured. The greatest daily weight gain were observed in the corn diet (T2). The pigs submitted to the wheat diet (T3) or cassava meal (T4) showed greater daily weight gain if compared to rice bran diet (T1). The feed to gain ratio was better on T4, intermediate on T2 and T3, which do not differ between each other (p>0,05), and showed the worst one T1. The carcass charactheristics were close to publicated standards and T4 presented 3 % more meat on carcass if compared to T2. The pH1 e pHu on loin and leg meat were not different (p>0,05) between treatments and are in concordance with the literature. On leg meat, independently of treatment, colour and WHC presented normal values, and there is a positive relationship of 74 % between pHu and WHC; there were not detected difference (p>0,05) between treatments for humidity, fat and cholestherol. These determinated values were lower than the literature citations. The saturated fat was reduced with the alternative treatments, with the lowest values on T4. On meat and bacon the ratio of ω6 to ω3 were better on the alternative treatments, with better ratio on T4 (ratio of 9ω6/ω3 in meat). During the 28 days of salami maturation there occured a reduction on pH because of lactic acid formation and were observed an increasingly enhance of pigmentation. On salami, after its production, occured an increase (p≤0,05) in fat content on T1, but on average the treatments showed a reduction in 47% to 51,5% if compared to data of the literature; protein content was increased between 8 % and 22,6 % if compared with literature values. On salami shelf life at 120 days there was: reduction on fat content on T4 if compared with T1 and T2 (p≤0,05); lower cholestherol values on alternative treatments; better ω6/ω3 ratios on T3 and T4; an increase (p≤0,05) of 35,15% on total volatiles compounds in T1. The microbiological counting of raw material was low, allowing the lactic bacteria to prevail the contaminant ones, and on salami shelf life the counting was within the tolerance levels. In sensorial analisys, after maturation and after shelf life, the salami, obtained "good" grade evaluation, which results in its acceptance. One can conclude: Alternative ingredients as rice bran, wheat and cassava meal may be used as substitutes of corn during growth and in final growing pigs with reduction of feeding costs; the carcass quality, bacon and leg meat received influence of the treatments; the raw material, obtained with the feeding of alternative ingredients, when used on salami production held or improved their volatiles physicochemical, hundredth, microbiologic and sensorial charactheristics, the alternative treatments improved the ratio of ω6/ω3 and lowered the saturated fat on fresh meat, bacon and salami, reducing the cholestherol in these products in relation to the published literature.